2015
DOI: 10.1016/j.ajog.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of race/ethnicity and BMI on the association between height and risk for spontaneous preterm birth

Abstract: OBJECTIVE Short height and obesity have each been associated with increased risk for preterm birth (PTB). However, the effect of short height on PTB risk, across different race/ethnicities and BMI categories, has not been studied. Our objective was to determine the influence of maternal height on the risk for PTB within race/ethnic groups, BMI groups, or adjusted for weight. STUDY DESIGN All California singleton, live births between 2007–2010 were included from birth certificate data (vital statistics) linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
4
13
0
Order By: Relevance
“…Our findings are consistent with those of a recent study conducted in California, which showed that patterns of association between height and risk of spontaneous PTB varied according to the maternal ethnicity. 11 In the present study, an inverse significant association between height and risk of PTB was found for Belgians, Italians and Polish. However, this association was not observed for women from Congo, France, Morocco, Romania or Turkey.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Our findings are consistent with those of a recent study conducted in California, which showed that patterns of association between height and risk of spontaneous PTB varied according to the maternal ethnicity. 11 In the present study, an inverse significant association between height and risk of PTB was found for Belgians, Italians and Polish. However, this association was not observed for women from Congo, France, Morocco, Romania or Turkey.…”
Section: Discussionsupporting
confidence: 54%
“… 6 9 10 These mixed results could be partly due to varying definitions of short stature or height cut-offs, variation in quality of studies, heterogeneous populations and small sample sizes in the subgroups. 11 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Height, impacted by the genetic, intrauterine, childhood, and environmental factors, is known to be associated with several diseases and conditions. [22][23][24][25][26][27][28] In pregnancy, height is inversely related to a modestly increased risk of spontaneous preterm birth, 27 gestational diabetes, 24 low infant birth weight, 25,26 length, 23 and possibly neural tube defects. 28 Height (inverse) has also been associated with the overall risk of cardiovascular disease, coronary heart disease, stroke, and heart failure, whereas it is directly related to the risk of pulmonary embolism and ruptured aortic aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that maternal characteristics such as an obstetric history, prior cervical excisional procedure, and maternal weight and height, confer a high risk of preterm birth ( 10 11 12 13 14 15 ). However, the causality between these maternal characteristics and preterm birth remains unclear because most of the prior studies explained the relationship by using other confounders such as an obstetric history, weight, height, and a history of alcohol or substance abuse; but not included short CL.…”
Section: Introductionmentioning
confidence: 99%